Climate change affects rainfall patterns in crop-producing regions: Findings from the study “Emergence of robust precipitation changes across crop production areas in the 21st century" - Rojas Corradi, Maisa; Lambert, Fabrice; Ramírez Villegas, Julián Armando; Challinor, Andrew J. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2019)
Rain-fed agriculture currently constitutes 60–95% of farmed land across the developing world. Changing rainfall patterns could have a large impact on agriculture in developing countries. Using over 20 different climate models, researchers have projected how precipitation could be affected by climate change. Key takeaways include: 1) unless emissions are curbed soon, by 2040, the rainfall patterns in many major wheat, soybean, rice and maize regions will have changed outside their natural boundaries; 2) emissions reductions in accordance with the Paris Agreement would result in far less crop-producing areas experiencing novel rainfall patterns; and 3) targeting adaptation efforts remains a major challenge, but region specific results can now enable investment and action.